Penguatan Karakter Siswa Melalui Workshop Puisi - Desi Rahmawati; Darwin Effendi; Desi Ashari; Gika Adinda Febriani; Luvia Karfika; Abel Dwi Syarani; Isyiqa Octa Ramadhani; Sinta Utari; Kadek Vika Elisa (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Character education is one of the primary focuses in developing the quality of human resources, as it emphasizes not only the acquisition of knowledge but also the formation of students’ attitudes, morals, and behaviors. One alternative approach to strengthening character education is through poetry workshops, which integrate reflection, creativity, and social interaction. This article aims to describe the implementation of a poetry workshop and analyze its contribution to strengthening students’ character. The study employed a descriptive qualitative approach, with data collected through participant observation, semi-structured interviews, and document analysis of the participants’ poetry works. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the poetry workshop was conducted in three stages: introducing the concept of poetry, practicing poetry writing based on personal experiences, and collaboratively presenting and appreciating participants’ works. These stages contributed to fostering creativity, enhancing self-confidence, developing empathy, and strengthening participants’ ability to express life values through literary works.